A Seal Impression of ‘ShemaꜤ Servant of Jeroboam’ - Aḥituv, Shmuel (Tel Aviv, 2023)
The article deals with a small bulla of unknown provenance that was purchased some forty years ago in the Bedouin market of Beʾer Sheva. The bulla was stamped with a seal depicting a roaring lion, above which the letters (LSM[Ꜥ]) were straightforwardly identified; it closely resembles the famous ‘ShemaꜤ servant of Jeroboam’ seal from Megiddo. Significantly, this unique bulla represents, to date, the first example of an ancient bulla stamped with a scaled-down authentic seal of a known master-seal of the Iron Age in Israel. The authenticity of the bulla was confirmed by meticulous laboratory tests, verifying both that it is genuine and that its date coincides with that of the ShemaꜤ seal from Megiddo.